A retrospective study of spontaneous intracranial hemorrhage - Wahjoepramono, Eka J. (Universa Medicina, 2009)
Spontaneous intracerebral hemorrhage (SICH) is a serious disease despite progressing medical knowledge. SICH appears suddenly without warning, unlike ischemic strokes that are often preceded by a transient ischemic attack. Outcome is determined by the initial severity of the bleeding; mortality and morbidity of SICH are high. The aim of this study was to describe the characteristics of type, location, and outcome of SICH. A retrospective review was conducted on the records of 2042 cases admitted to a private hospital in Karawaci, Tangerang, between 1 January 1996 to 31 December 2008. Analysis was done on type, location, and the final outcome measures by the Glasgow Outcome Scale (GOS). The results of the study showed that the most prevalent type of SICH was hypertensive stroke, amounting to 1698 cases (83.1%), and the least commonly encountered type was dural fistula totalingÂ  5 cases (0.3%). SICH due to hypertensive stroke frequently occurred in the basal ganglia (50.8%) comprising the putamen, caudate nucleus and globus pallidus. On average, the outcome at the time of dismissal was good, where 105 cases (88.2%) were GOS 4 and 5. SICH requires prompt and appropriate management. Therefore the signs and symptoms of intracranial hemorrhage should be promptly recognized and followed by appropriate ancillary examinations in order to promptly determine the management required, including possible surgical interventions.